Do apóstolo ao peregrino: a iconografia de São Tiago na escultura devocional medieval em Portugal - Begoña Farré Torras (Medievalista)
The purpose of this article is to explore the evolving iconography of Saint James the Greater, as a pilgrim, in medieval votive sculpture in Portugal. The first part of the text focuses on the origins of this figuration in an Iberian context, taking into account two lines of influence: the iconography of Christ himself as a pilgrim, and popular imagery. The study then proceeds to the serial analysis of a corpus of devotional images in order to trace their evolution in Portugal between the 14th and the 16th centuries, and concludes by reflecting on the symbolic values implicit in this kind of figuration.